2020
DOI: 10.3390/su13010198
|View full text |Cite
|
Sign up to set email alerts
|

Implement an International Interoperable PHR by FHIR—A Taiwan Innovative Application

Abstract: Personal health records (PHRs) have lots of benefits for things such as health surveillance, epidemiological surveillance, self-control, links to various services, public health and health management, and international surveillance. The implementation of an international standard for interoperability is essential to accessing personal health records. In Taiwan, the nationwide exchange platform for electronic medical records (EMRs) has been in use for many years. The Health Level Seven International (HL7) Clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 29 publications
(32 reference statements)
0
9
0
Order By: Relevance
“…FIHR follows the modular approach and represents the atomic healthcare data (i.e., medication, blood pressure, allergies) as independent entities called resources. All of these resources are managed (i.e., created, shared, and updated) via APSs and web services (RESTful web service) [87]. A systematic review about medical data interoperability reported that FHIR is one of the messaging standards that most satisfied the requirement of healthcare interoperability and provided several client-side features (i.e., privacy, reliability, security, flexibility, and compatibility) [88].…”
Section: Back-end System Knowledge Basementioning
confidence: 99%
“…FIHR follows the modular approach and represents the atomic healthcare data (i.e., medication, blood pressure, allergies) as independent entities called resources. All of these resources are managed (i.e., created, shared, and updated) via APSs and web services (RESTful web service) [87]. A systematic review about medical data interoperability reported that FHIR is one of the messaging standards that most satisfied the requirement of healthcare interoperability and provided several client-side features (i.e., privacy, reliability, security, flexibility, and compatibility) [88].…”
Section: Back-end System Knowledge Basementioning
confidence: 99%
“…The one developed by Ruminski et al [ 46 ], Saripalle [ 47 ], and Yu et al [ 48 ] intended to support multiple Internet of Things protocols. Finally, the one discussed in the studies by Khvastova et al [ 49 ], Dridi et al [ 50 ], Lee et al [ 51 ], Tanaka and Yamamoto [ 52 ], Cheng et al [ 53 ], Semenov et al [ 54 ], and Gruendner et al [ 55 ] was used to support data preprocess plug-ins.…”
Section: Resultsmentioning
confidence: 99%
“…In line with our study, in the study of Ibrahim et al, the web-based ASP.NET framework was used to provide a data exchange model for patients’ records to reduce patients’ time and cost and enable physicians to obtain up-to-date and accurate information from patients’ records ( 39 ). In the study of Lee et al, ASP.NET was used to set up a platform for displaying, transferring data, accepting databases, and converting personal health record formats ( 42 ). Studies have shown that web-based EHRs allow access to and exchange of information such as patient name, history, illness, physical examination, health assessment, patient condition, quality of life, and patient care ( 43 ).…”
Section: Discussionmentioning
confidence: 99%